Linolenic Acid Attenuates the Vasodilation Induced by Acetylcholine in Isolated Rat Aortae. Issue 4 (6th December 2019) - Lee, Soo Hee; Ok, Seong-Ho; Kim, Ji-Yoon; Subbarao, Raghavendra Baregundi; Bae, Sung Il; Hwang, Yeran; Park, Kyeong-Eon; Kim, Jong Won; Sohn, Ju-Tae
This study aims to examine the effect of linolenic acid on the vasodilation or vasoconstriction induced by acetylcholine and bupivacaine in isolated rat aortae and its underlying mechanism. The effect of linolenic acid on the vasodilation induced by acetylcholine, the calcium ionophore A23187, sodium nitroprusside, and 8-bromoguanosine 3′, 5′-cyclic monophosphate sodium salt (bromo-cyclic guanosine monophosphate [bromo-cGMP]) in endothelium-intact and endothelium-denuded aortae was examined. Linolenic acid inhibited vasodilation induced by acetylcholine, calcium ionophore A23187, and sodium nitroprusside. However, this fatty acid increased bromo-cGMP-induced vasodilation in endothelium-denuded aortae. Linolenic acid increased bupivacaine-induced contraction in endothelium-intact aortae, whereas it decreased bupivacaine-induced contraction in endothelium-intact aortae with N ω -nitro-l -arginine methyl ester and endothelium-denuded aortae. Linolenic acid inhibited acetylcholine- and bupivacaine-induced phosphorylation of endothelial nitric oxide synthase. Sodium nitroprusside increased cGMP in endothelium-denuded aortic strips, whereas bupivacaine decreased cGMP in endothelium-intact aortic strips. Linolenic acid decreased cGMP levels produced by bupivacaine and sodium nitroprusside. Together, these results suggest that linolenic acid inhibits acetylcholine-induced relaxation by inhibiting a step just prior to nitric oxide-induced cGMP formation. In addition, linolenic acid-mediated inhibition of vasodilation induced by a toxic concentration (3 × 10 −4 M) of bupivacaine seems to be partially associated with inhibition of the nitric oxide–cGMP pathway.